The Climate-Smart Villages – CSV of Santa Rita as a local innovation platform for scaling ecosystem- based adaptation in Honduras - Martinez Salgado, Jesus David; Borrayo, Andrea Surama; Cindy, Gómez; Castellanos, Andrea; Martinez Baron, Deissy (2025)
The municipality of Santa Rita (Honduras), located in the Central American Dry Corridor region, is characterized by irregular rainfall and high vulnerability to climate variability (FAO, 2019). According to IPCC models (2013), this area is particularly susceptible to the effects of climate change. The recurrence of phenomena such as droughts has led farmers to intensify the use of natural resources to sustain or increase their incomes and ensure their food security (Calvo-Solano et al., 2018). However, this excessive exploitation has triggered a harmful cycle, where inefficiency in managing environmental resources reduces the resilience of agri-food systems (FAO, 2023), affecting farming families’ incomes and limiting their ability to improve their living conditions. based Adaptation Fund (Global EbA Fund). The Climate Smart Villages – CSV in English, according to Aggarwal et al., 2018), established in Santa Rita since 2015, integrates research for development to address specific agro-climatic challenges faced by rural producers. This approach seeks to strengthen communities’ capacity to reduce their climate vulnerability by increasing their knowledge and adopting informed and sustainable measures related to soil conservation and management, water, biodiversity, the use of local agro-climatic information, emission reduction measures, and adaptation plans contextualized to the specific needs of families and communities through a participatory and inclusive process.